Analisis Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) pada Anak-Anak di Rumah Asuh YABNI Padang - Huvaid, Sevilla Ukhtil; Zia, Hanim Khalida (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
Clean and Healthy Living Behavior (PHBS) is a form of community empowerment that is aware, willing and able to practice PHBS. YABNI Padang Foster Home is a foster home/dormitory which not only functions as a residence but also as a base for services, coaching, a means of development and maturation as well as a place to practice skills as a provision to achieve the dreams of foster children. The aim of this research is to conduct an analysis of the application of PHBS to foster children at the YABNI Padang Orphanage. The type of research used is analytical research using a cross sectional design. The population unit in this study is 45 foster children residing in the YABNI Padang Orphanage. Data analysis in this study used bivariate analysis with the chi square test. The results of research regarding the implementation of PHBS at the YABNI Padang Foster Home can be concluded that there is a significant relationship between the variables of knowledge (p=0.028), attitude (p=0.024), availability of facilities (p=0.027) and the role of foster siblings/managers (p=0.011) with the implementation of PHBS at the YABNI Padang Orphanage. Therefore, it is necessary to create behavior change communication by increasing the active role of foster siblings/managers in efforts to implement PHBS through providing education and providing the health facilities needed to implement PHBS. Apart from that, it is also necessary to carry out routine and timely supervision of the entire series of PHBS activities so that the activities are right on target and in accordance with the predetermined schedule.